Attitudes of clinical psychologists towards clients with personality disorders - Egan, Sarah; Haley, S.; Rees, Clare (John Wiley & Sons Ltd., 2014)
Previous studies have found that a variety of mental health professionals hold negative attitudes towards clients diagnosed with a personality disorder. These negative attitudes may lead to clients receiving a lower quality of service. Specialist training has been found to improve attitudes towards personality disorders but no empirical studies in Australia have examined this among clinical psychologists. In this study, the attitudes of 81 clinical psychologists towards clients with personality disorders were examined. We were specifically interested in investigating the relationship between recency of specialist training and clinician’s attitudes as well as the influence of percentage of personality disorder clients on the clinician’s caseload. Results demonstrated that both recency of specialist training and percentage of clients seen were associated with more positive attitudes; however, a higher caseload of clients with personality disorders was the most important predictor of positive attitudes. The implication is that recent participation in specialist training for personality disorders appears to be valuable in improving clinician’s attitudes but that more positive attitudes are associated with seeing a greater number of individuals with personality disorders.